1983
DOI: 10.1136/jmg.20.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Microcephaly and intracranial calcification in two brothers

Abstract: The unrelated healthy parents requested genetic counselling after the birth of the first affected child. They had a normal girl. In view of the combination of severe retardation, microcephaly, and intracranial calcification, an intrauterine infection was considered, although no confirmation of this was found. A lowish recurrence risk was given. The mother then became pregnant again and the fetal head circumference was measured at 17, 20, and 25 weeks and compared with the abdominal circumference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 9 publications
1
45
0
Order By: Relevance
“…Narrowly-defined pseudo-TORCH syndrome (al-Dabbous et al, 1998;Baraitser et al, 1983;Briggs et al, 2008;Burn et al, 1986;Cohen et al, 2012;Ishitsu et al, 1985;Knoblauch et al, 2003;Kulkarni et al, 2010;Nakamura et al, 2011;Reardon et al, 1994;Vivarelli et al, 2001;Watts et al, 2008;Wieczorek et al 1995), also called Baraitser-Reardon syndrome (Vivarelli et al, 2001), or band-like calcification with simplified gyration and polymicrogyria (BLCPMG; MIM: 251290) (Abdel-Salam & Zaki, 2009;Briggs et al, 2008;O'Driscoll et al, 2010), is associated with microcephaly and intracranial calcifications mimicking congenital toxoplasmosis in the absence of infection. Ocular changes are not reported with pseudo-TORCH syndrome / AGS.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Narrowly-defined pseudo-TORCH syndrome (al-Dabbous et al, 1998;Baraitser et al, 1983;Briggs et al, 2008;Burn et al, 1986;Cohen et al, 2012;Ishitsu et al, 1985;Knoblauch et al, 2003;Kulkarni et al, 2010;Nakamura et al, 2011;Reardon et al, 1994;Vivarelli et al, 2001;Watts et al, 2008;Wieczorek et al 1995), also called Baraitser-Reardon syndrome (Vivarelli et al, 2001), or band-like calcification with simplified gyration and polymicrogyria (BLCPMG; MIM: 251290) (Abdel-Salam & Zaki, 2009;Briggs et al, 2008;O'Driscoll et al, 2010), is associated with microcephaly and intracranial calcifications mimicking congenital toxoplasmosis in the absence of infection. Ocular changes are not reported with pseudo-TORCH syndrome / AGS.…”
Section: Overviewmentioning
confidence: 99%
“…These signs include microcephaly (Aalfs et al, 1995;Abdel-Salam & Zaki, 2009;AbdelSalam et al, 1999;Abdel-Salam et al, 2000;Ahmadi & Bradfield, 2007;Aicardi & Goutières, 1984;al-Dabbous et al, 1998;al-Gazali et al, 1999;Alzial et al, 1980;Angle et al, 1994;Atchaneeyasakul et al, 1998;Baraitser et al, 1983;Bogdan, 1951;Book et al, 1953;Briggs et al, 2008;Burn et al, 1986;Cantú et al, 1977;Casteels et al, 2001;Dale et al, 2000;EventovFriedman et al, 2009;Feingold & Bartoshesky 1992;Fisch et al, 1973;Fryns et al, 1995;Hoyeraal et al, 1970;Hordijk et al, 1996;Hreidarsson et al, 1988;Ishitsu et al, 1985;Jarmas et al, 1981;Kloepfer et al, 1964;Knoblauch et al, 2003;Komai et al, 1955;Kozma et al, 1996;Kulkarni et al, 2010;Leung, 1985;Limwongse et al, 1999;McKusick et al, 1966;Mishra et al, 2002;Nakamura et al, 2011;Nemos et al, 2009;Ostergaard et al, 2012;Pearson et al, 2008;Reardon et al, 1994;…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only Qazi and Reed (1973) found that epilepsy is four times more frequent in individuals with SMC. In addition, seizures have been reported in one-third of those with PMC (Baraitser et al 1983). The present study attempts to (1) provide a classification for MC; (2) to determine the prevalence of epilepsy in different types of MC; (3) to characterize the EEG manifestations in different types of MC; and (4) to see whether there is a correlation between EEG, seizure type, and control by antiepileptic drugs.…”
mentioning
confidence: 99%